Achieving Sustainable Development in Respective County Governments in Kenya Through Market Failures and Sustainable Business Entrepreneurship Initiatives - ORIBU, WILLIAM SAGINI (Archives of Business Research, 2022)
Devolution has been considered as a key pillar of the Constitution of Kenya since the concept seeks to bring governance closer to the people. In line with the Constitution of Kenya 2010 county governments are now at the centre of dispersing political power and economic resources to specific communities. The Principles that underpin devolution in Kenya are that County governments established under the Constitution shall have reliable sources of revenue to enable them govern and deliver services effectively. This study seeks to examine how the principles of entrepreneurship and the issue of market failures can be harnessed by county governments to improve the economic wellbeing in their respective communities. On one hand, environmental economists argue that market failures bring about environmental degradation while on the other hand available literature on entrepreneurship argues that business opportunities arise from market failures. Environmental entrepreneurship details how entrepreneurs seize opportunities that arise from environmentally relevant market failures in order to succeed. Entrepreneurship literature therefore analyses how environmentally relevant market failures may represent opportunities for the achievement of business profitability. This being the case, then businesses can use part of the profits earned for corporate social responsibility in order to reduce environmental degrading economic behaviours. When there are increases in the quality of life and economic growth, there will be substantial negative effects on the natural environment which will diminish the sustainability of most economic systems. This conceptual paper looks at the entrepreneurship as a concept that can be applied in the management of community resources in order to achieve sustainable development and improve the welfare of its citizens. The paper recommends that the administration of county governments in Kenya need to study the environmental failures in their areas of jurisdiction to institute studies on how these failures can be utilised as opportunities for the improvement of the economic wellbeing of the citizens. In order to do these, entrepreneurship concept will become very handy in the said studies.